PROSEDUR PENYUSUNAN DOKUMEN PELAKSANAAN ANGGARAN (DPA) DAN ANGGARAN KAS SATUAN KERJA PERANGKAT DAERAH (SKPD) MENGGUNAKAN SISTEM INFORMASI PEMERINTAH DAERAH (SIPD) PADA DINAS PENANAMAN MODAL DAN PELAYANAN TERPADU SATU PINTU (DPM-PTSP) PROVINSI JAMBI - Sinulingga , Nafisa Desfania Br.; Putra, Dios Nugraha (Jambi Accounting Review (JAR), 2025)
This study aims to analyze the procedure for preparing the Budget Implementation Document (DPA) and the Cash Budget of Regional Work Units (SKPD) using the Regional Government Information System (SIPD) at Dinas Penanaman Modal dan Pelayanan Terpadu Satu Pintu Provinsi Jambi and to evaluate its compliance with prevailing regional financial management regulations. A descriptive qualitative approach was employed, with data collected through observation, interviews, and documentation review.The findings indicate that the preparation of the DPA and Cash Budget has been conducted systematically through the delegation of authority to the Budget User Proxy (KPA), the assignment of Technical Activity Implementation Officers (PPTK), the preparation of the Cash Budget Plan (RAK), and the verification process within SIPD. The implementation of SIPD has improved data accuracy, time efficiency, information integration, and transparency in regional financial governance.